Hubungan Stres, Kualitas Tidur Dan Emotional Eating Dengan Status Gizi Pada Mahasiswa Tingkat Akhir Program Studi S1-Ilmu Gizi Ikbis Surabaya - Alpian Jayadi; Fidatul Jamila; Zummatul Atika; Sri Wahyuni (Departement of Mathematics Education, 2024)
Final year students can experience stress caused by several factors that can come from academic life, such as course load, getting a good GPA and plus working on a thesis as a graduation requirement. This study was conducted to determine the relationship between stress, sleep quality and emotional eating with the nutritional status of final year students of the IKBIS Surabaya Nutrition Science Study Program. This type of research is analytical observational with a Cross Sectional approach. The sample in this study amounted to 35 final year students. Stress data was measured using the Perceived Stress Scale (PSS) questionnaire, sleep quality data was measured using the Pittsburgh Sleep Quality Index (PSQI) questionnaire, emotional eating data was measured using the Adult Eating Behaviour Questionnaire (AEBQ) and nutritional status was measured using BMI. Data were analyzed using the Chi-Square test. It was found that 11.4% of students experienced undernutrition and 25.7% of students experienced overnutrition. As many as 40% of students experience stress, 94.3% have poor sleep quality and as many as 54,3% of students experience emotional under eating, while 14,3% of students experience emotional over eating. There is no significant relationship between stress, sleep quality and emotional eating with nutritional status respectively (p= 0,609; 0,281; 0,920 dan 0,791). Stress, sleep quality and emotional eating are not significantly associated with nutritional status in final year students of the IKBIS Surabaya Nutrition Science S1 Study Program.